Collagen-coated 3D-TechTra scaffold integrated with human umbilical cord mesenchymal stem cells enhances tracheal tissue regeneration and reduces stenosis in rabbit models - Yahaya, Badrul Hisham; Abu Bakar, Nur Fitriyani Afiqah; Samat, Asmak Abdul; Ishtiah, Anan A.; Mohamad Yusof, Loqman; Abdul Hamid, Zuratul Ain; Osman, Noor Diyana; Khalil, Nor Azlina; Mohd Radzi, Rodiah; Musa, Muhamad Yusri; Jaafar, Mariatti (Huazhong University of Science and Technology, 2025)
Objective: This study aimed to evaluate the potential of a collagen-coated, 3D-printed tracheal scaffold (3D-TechTra) integrated with human umbilical cord mesenchymal stem cells (hUC-MSCs) for tracheal tissue regeneration. Methods: The thermoplastic polyurethane/polylactic acid (TPU/PLA) scaffold was engineered to optimize mechanical properties and biocompatibility, with the goal of mimicking the structural and tensile characteristics of native tracheal tissue. Subsequently, preclinical experiments were conducted using rabbit models: the performance of the collagen-coated TPU/PLA scaffold with hUC-MSCs was compared with that of uncoated scaffolds and collagen-only scaffolds. In vitro tests were also performed to assess the adhesion, proliferation, and differentiation of hUC-MSCs on the scaffold. For in vivo evaluation, multiple analytical methods were employed, including immunohistological analysis (to detect glycosaminoglycan deposition and extracellular matrix remodeling), radiographic and endoscopic evaluations (to assess tracheal contour and airway obstruction), and survival analysis (to monitor animal outcomes and systemic toxicity). Results: In vitro, hUC-MSCs successfully adhered to and proliferated on the TPU/PLA scaffold, and differentiated into adipogenic, osteogenic, and chondrogenic lineages, which supported the potential for tissue-specific regeneration; in vivo, compared with uncoated or collagen-only scaffolds, the collagen-coated TPU/PLA scaffold integrated with hUC-MSCs exhibited enhanced integration with host tissues, superior biocompatibility, and reduced tracheal stenosis, while also preserving airway patency, alleviating inflammation, and facilitating epithelial regeneration, smooth muscle formation, and vascularization. Immunohistological analysis further revealed significant glycosaminoglycan deposition and extracellular matrix remodeling in the hUC-MSC-treated group, and radiographic and endoscopic evaluations confirmed preserved tracheal contour and reduced airway obstruction; additionally, survival analysis showed significantly improved outcomes in animals treated with the collagen-coated TPU/PLA scaffold containing hUC-MSCs, with no systemic toxicity observed. Conclusions: This study demonstrated the synergistic potential of TPU/PLA scaffolds, collagen coatings, and hUC-MSCs, providing valuable evidence for advancing the application of these components in tracheal tissue engineering.